Study of the potential toxicity of adrenaline to neurons, using the SH-SY5Y human cellular model - Vera Marisa Costa; João Paulo Capela; Maria Lourdes Bastos; Fernando Remião; Kurt James Varner; José Alberto Duarte; Félix Carvalho (Universidade de São Paulo, 2023)
Abstract Prolonged overexposure to catecholamines causes toxicity, usually credited to continuous adrenoceptor stimulation, autoxidation, and the formation of reactive pro-oxidant species. Non-differentiated SH-SY5Y cells were used to study the possible contribution of oxidative stress in adrenaline (ADR)-induced neurotoxicity, as a model to predict the toxicity of this catecholamine to peripheral nerves. Cells were exposed to several concentrations of ADR (0.1, 0.25, 0.5 and 1mM) and two cytotoxicity assays [lactate dehydrogenase (LDH) release and 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyl tetrazolium bromide (MTT) reduction] were performed at several time-points (24, 48, and 96h). The cytotoxicity of ADR was concentration- and time-dependent in both assays, since the lowest concentration tested (0.1mM) also caused significant cytotoxicity at 96h. N-acetyl-cysteine (1mM), a precursor of glutathione synthesis, prevented ADR-induced toxicity elicited by 0.5mM and 0.25mM ADR following a 96-h exposure, while the antioxidant Tiron (100µM) was non-protective. In conclusion, ADR led to mitochondrial distress and ultimately cell death in non-differentiated SH-SY5Y cells, possibly because of ADR oxidation products. The involvement of such processes in the catecholamine-induced peripheral neuropathy requires further analysis.